2016
DOI: 10.1017/s1355617716000965
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Memory Dysfunction during High Altitude Hypoxia Training in Military Aircrew

Abstract: Objectives Cognitive dysfunction from high altitude exposure is a major cause of civilian and military air disasters. Pilot training improves recognition of the early symptoms of altitude exposure so that countermeasures may be taken before loss of consciousness. Little is known regarding the nature of cognitive impairments manifesting within this critical window when life-saving measures may still be taken. Prior studies evaluating cognition during high altitude simulation have predominantly focused on measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…These results add to the accumulating body of evidence that the CDN group – which accounts for a significant proportion of the ADNI MCI cohort – represents false positive diagnostic errors (Bangen et al, 2016; Bondi et al, 2014; Edmonds et al, 2014, 2015, 2016; Eppig et al, 2017; Thomas et al, 2017). Previous studies have suggested that MCI patients have intact awareness of their cognitive abilities (for review, see Piras et al, 2016), which appears contrary to our results.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…These results add to the accumulating body of evidence that the CDN group – which accounts for a significant proportion of the ADNI MCI cohort – represents false positive diagnostic errors (Bangen et al, 2016; Bondi et al, 2014; Edmonds et al, 2014, 2015, 2016; Eppig et al, 2017; Thomas et al, 2017). Previous studies have suggested that MCI patients have intact awareness of their cognitive abilities (for review, see Piras et al, 2016), which appears contrary to our results.…”
Section: Discussionsupporting
confidence: 59%
“…In stark contrast, participants who were determined to be cognitively normal on neuropsychological testing had a tendency to over-report cognitive difficulty at all three time points, with remarkable consistency in both self- and informant-report over time. This pattern was seen for both the robust NC group and for the CDN group – a large subtype of ADNI participants who have been intensively studied by our group and appear to be misdiagnosed with MCI based on conventional diagnostic criteria (Bangen et al, 2016; Bondi et al, 2014; Edmonds et al, 2014, 2015, 2016; Eppig et al, 2017; Thomas et al, 2017). …”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations